Conversor CC-CC elevador de tensão Full-Bridge para aplicações em célula a combustível - Faria, Julliano Henrique Santos de (2012)
This paper presents the study and implementation of a power conditioning system Fuel Cells low power in order to supply the DC link inverter systems connected to the network. We analyze the conditions for generation of fuel cell and those imposed by the application, which must be addressed in the operation of the converter and also presented some justifications for choosing the Full-Bridge Converter. The details of the converter design, including aspects of the plant and of its closedloop control, which is implemented in digital form as a platform using a digital signal processor fixed point. In order to analyze the performance of the converter designed are presented simulation and experimental results.